Vibration Analysis of Laminated Composite Plate under Thermo- Mechanical Loading (Journal of Engineering, 2014)
The present study focused mainly on the vibration analysis of composite laminated plates subjected tothermal and mechanical loads or without any load (free vibration). Natural frequency and dynamicresponse are analyzed by analytical, numerical and experimental analysis (by using impact hammer) fordifferent cases. The experimental investigation is to manufacture the laminates and to find mechanicaland thermal properties of glass-polyester such as longitudinal, transverse young modulus, shear modulus,longitudinal and transverse thermal expansion and thermal conductivity. The vibration test carried tofind the three natural frequencies of plate. The design parameters of the laminates such as aspect ratio,thickness ratio, boundary conditions and lamination angle were investigated using classical laminatedplate theory (CLPT) and Finite element coded by ANSYS, in addition to the design parameters ofdynamic response such as load type with respect to time, x and y dimension and temperature value forsimply supported symmetric cross ply. The main conclusion was the natural frequency could increaseand decrease depending on the boundary conditions, thickness ratio, and lamination angle, the aspectratio of the plate. Present of temperature could increase dynamic response of plate also depending onlamination angle, type of mechanical load and the value of temperature.